The alarming history of medicine - Gordon, Richard, 1921- (ew York : St. Martin's Griffin, 1997)
Gathers the real stories behind discoveries in medicine and humorous anecdotes about early cures and procedures.
"First published in Great Britain by Sinclair-Stevenson Limited"--T.p. verso.
Includes bibliographical references (p. 250-256).
Keywords: Medicine -- Anecdotes; Therapeutics -- Anecdotes